PENGARUH RETURN ON ASSET, EARNING PER SHARE, DAN TOTAL ARUS KAS TERHADAP HARGA SAHAM - Febri Angraeni; Eny Purwaningsih (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
This research uses a type of comparative causal research which is used to determine the causal relationship of two or more variables. The sample in this study is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2020 using the purposive sampling method. There are 17 companies that meet the research sample criteria so that a sample of 51 financial statement data is obtained. This research method uses multiple linear regression analysis. Based on the test results, it is known that it simultaneously shows that return on assets, earnings per share and total cash flow have a simultaneous effect on stock prices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Partial test results show that return on assets has a positive effect on stock prices, earnings per share has a positive effect on stock prices and total cash flow has no effect on stock prices.